The Influence of Serotonin on Clot Retraction and the Thrombelastogram - Deutsch, E; Martiny, K (Thrombosis and Haemostasis, 1958)
1. Normal platelets are necessary for induction of normal clot retraction.2. Serotonin does not induce retraction in human platelet-free plasma-clots or enhance clot firmness as measured in the coagulogram.3. Serotonin does not improve clot retraction or firmness in plasma clots with sub-optimal platelet counts.4. Methylserotonin inhibits clot retraction of platelet-rich plasma to a certain extent in moderate doses, whereas, high doses are ineffective. BOL 148 has a similar, but less significant action. There is a possibility that these effects are specific antiserotonin-effects.5. LSD 25 was ineffective in all concentrations used.6. Largactil and reserpin inhibit retraction in high doses. There seems to be a non specific effect caused by the high dose.7. Reserpine does not release a retraction-inducing agent from the platelets, which could be detected in the centrifuged platelet-free plasma used for the incubation.8. Serotonin does not replace the retraction-cofactor of Hartert, or the dialyzable factor of Lüscher in synthetic clotting substrates.9. Serotonin is of no essential value in inducing normal retraction of human plasma clots.